2021
DOI: 10.3389/fimmu.2021.712614
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Supplementation During Pregnancy Modifies the Gut Microbiota and Increases Metabolites in Amniotic Fluid, Driving a Tolerogenic Environment In Utero

Abstract: The gut microbiota is influenced by environmental factors such as food. Maternal diet during pregnancy modifies the gut microbiota composition and function, leading to the production of specific compounds that are transferred to the fetus and enhance the ontogeny and maturation of the immune system. Prebiotics are fermented by gut bacteria, leading to the release of short-chain fatty acids that can specifically interact with the immune system, inducing a switch toward tolerogenic populations and therefore conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…Remarkably, at 6 weeks of age, we still observe tolerance biomarkers in pups antenatally exposed to prebiotics, including an increase of Treg and Breg associated with an increased IL-10 secretion, and an increased Th1 and Th2 response. We have already demonstrated that in utero the consumption of prebiotics promotes a pro-tolerogenic environment (25), and herein we demonstrate that this immune environment endures at least until 6 weeks of life. The increase in Breg numbers might be explained by the increased abundance of Lactobacillus in the fecal microbiota, as this family has been shown to promote the differentiation of Breg in the spleen and in the mesenteric lymph nodes (49).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Remarkably, at 6 weeks of age, we still observe tolerance biomarkers in pups antenatally exposed to prebiotics, including an increase of Treg and Breg associated with an increased IL-10 secretion, and an increased Th1 and Th2 response. We have already demonstrated that in utero the consumption of prebiotics promotes a pro-tolerogenic environment (25), and herein we demonstrate that this immune environment endures at least until 6 weeks of life. The increase in Breg numbers might be explained by the increased abundance of Lactobacillus in the fecal microbiota, as this family has been shown to promote the differentiation of Breg in the spleen and in the mesenteric lymph nodes (49).…”
Section: Discussionsupporting
confidence: 69%
“…Microbial transfers between mother and child might trigger immune responses in the fetus and the newborn that might shape the infant's IS development, the notion of "early life imprinting" of the IS (48). In this context, we already published that prebiotic supplementation during gestation increased the frequency of tolerogenic immune cells (Treg and Breg) in feto-maternal tissues and increased the level of SCFAs in the amniotic fluid (25). Interestingly, the frequency of Breg was also increased in the intestine and femurs of fetuses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neonates demonstrate a complex microbiota in the gut within the week immediately following birth, with dynamic fluctuations in the composition of the gut microbiota until a stable adult microbiota composition is reached at the age of 2–2.5 years. Research suggests that facultative and aerotolerant bacteria such as lactic acid bacteria, Enterobacteria , and streptococci dominate the initial flora in the neonatal gut, followed by an increasing number of strict anaerobes, including Bifidobacterium, Clostridium, Bacteroides ( Bottacini et al, 2017 ; Milani et al, 2017 ; Brosseau et al, 2021 ).…”
Section: The Development Of the Gut Microbiotamentioning
confidence: 99%